(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تتطرق الدراسة بشكل رئيس إلى ظاهرة القطاع غير المنظّم، والتي تعتبر من أبرز القضايا التي تستدعي اهتمام الباحثين وصانعي السياسة الاقتصادية، نظراً لانتشارها الواسع في الاقتصاديات كافة (المتطورة، الناشئة، النامية)، وبالرغم من أهميتها فإن الدراسات التي تبحث فيها في البلدان النامية تعتبر محدودة وغير كافية.تبحث الدراسة في إطار المفاهيم المتعددة للقطاع غير المنظّم ومكونات هذا القطاع من الأنشطة ونواتج هذه الأنشطة من السلع والخدمات، وتبين أهم الأسباب التي تحّفز الأفراد لمزاولة الأنشطة غير المنظمة،مع التركيز على حالة سوريا، حيث توضّح الأثر الكبير لمعدلات النمو السكانية المرتفعة، وتدني مستويات الأجور الحقيقيّة، وصعوبة الدخول إلى مجال الأعمال في دفع الأفراد نحو القطاع غير المنظّم، وإضافةً لتبيان ما يترتب على وجود هذا القطاع من آثار اجتماعية واقتصادية وغيرها. The study mainly handles the informal sector phenomenon which is the most prominent issues that require researches and economic policy makers, due to widespread economical (developed, transitional, and developing countries) Despite the importance of the informal sector, the studies about it in developing countries are limited and inadequate. The study examines the context of diverse aspects of informal sector, the components, and outputs of informal activities of goods and services. The study identifies the most important reasons that motivate individuals to be engaged in informal activities, with a focus on the case of Syrian economy, reflecting the main causes such as, low wages rate, high population rate and difficulty of starting business. In addition, the economic and social consequences of informal sector have been discussed.